2004
DOI: 10.1038/sj.bmt.1704461
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 100-day mortality rates associated with i.v. busulfan and cyclophosphamide vs other preparative regimens in allogeneic bone marrow transplantation for chronic myelogenous leukemia: Bayesian sensitivity analyses of confounded treatment and center effects

Abstract: Summary:We evaluated the 100-day mortality rates associated with busulfan-based myeloablative conditioning regimens based on data from 1812 chronic myelogenous leukemia patients who underwent allogeneic blood or marrow transplantation (allotx). In all, 47 patients received intravenous (i.v.) busulfan and cyclophosphamide (i.v.BuCy2) with allotx at MD Anderson Cancer Center (MDACC) during 1995-1999. The remaining 1765 patients, whose data were supplied by the International Bone Marrow Transplant Registry (IBMTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…In the referenced study, nonrelapse mortality at 100 days after transplantation was 12% after related and 13% after MUD transplantations. Nonrandomized comparisons between patients treated with intravenous BuCy2 and those receiving unadjusted oral BuCy or TBI-based therapy appear to favor the intravenous busulfan-based conditioning regimen, 7,8,43 although definitive data from randomized studies are lacking. We hypothesized that the more precise dose delivery achieved with intravenous busulfan and a tighter …”
Section: Discussionmentioning
confidence: 99%
“…In the referenced study, nonrelapse mortality at 100 days after transplantation was 12% after related and 13% after MUD transplantations. Nonrandomized comparisons between patients treated with intravenous BuCy2 and those receiving unadjusted oral BuCy or TBI-based therapy appear to favor the intravenous busulfan-based conditioning regimen, 7,8,43 although definitive data from randomized studies are lacking. We hypothesized that the more precise dose delivery achieved with intravenous busulfan and a tighter …”
Section: Discussionmentioning
confidence: 99%
“…BU were the traditional four times daily dosing. 3,7,9,11,12 In recent years, studies have shown that once-daily i.v. BU had the same clinical efficacy as i.v.…”
Section: Introductionmentioning
confidence: 99%
“…BU has been proven to have better bioavailability, reliable systemic drug exposure with more predictable blood levels and lower toxicity than oral BU. [1][2][3][4][5][6][7][8][9][10] I.v. formulation of BU has become the preferred option in conditioning treatment for HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Also it has been reported to decrease the incidence of hepatic SOS compared with oral BU, therefore decreasing morbidity and mortality after allo-HSCT. 15,[19][20][21][22][23] The pathogenesis of SOS is thought to involve chemotherapy and radiation-induced damage to the sinusoidal endothelium, resulting in endothelial injury, microthrombosis, subendothelial damage and cytokine activation. 24,25 Severe SOS is typically associated with multi-organ failure and high mortality.…”
Section: Introductionmentioning
confidence: 99%